OPTIMALISASI DAKWAH KEMANUSIAAN PIMPINAN DAERAH AISYIYAH KABUPATEN BIMA MELALUI EDUKASI LEPRA DAN BUDAYA KONSUMSI BUAH BAGI MASYARAKAT BIMA - Rahmawati; Husnatul Mahmudah; Zuhrah; Mega Oktaviany; Aman Maarij; Nurfitriani; Gufran; Nasrullah; Bulqis (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
Bima Regency, West Nusa Tenggara, recorded a leprosy incidence rate of 4.7 per 10,000 population in 2023, far exceeding the national elimination threshold of less than 1 per 10,000 established by the Indonesian Ministry of Health. This epidemiological situation is compounded by micronutrient deficiencies, particularly vitamin C and zinc found in local fruits, which play a crucial role in maintaining cellular immunity against Mycobacterium leprae. This community service aimed to optimize the humanitarian da'wah capacity of the Aisyiyah Regional Board (PDA) of Bima Regency through two integrated interventions: community-based education on early detection, prevention, and leprosy destigmatization; and strengthening the local fruit consumption culture as an immunonutrition strategy rooted in local wisdom. The methodological approach employed was Community-Based Participatory Action Research (CBPAR) involving 128 Aisyiyah cadres, 64 registered leprosy patients, and 240 family members from eight sub-districts over six months. The conclusion results show an increase in knowledge about leprosy by 67.4% (p<0.001), a decrease in community stigma scores by 41.2% based on the Explanatory Model Interview Catalogue–Stigma (EMIC-S) instrument, and an increase in the frequency of daily fruit consumption by 53.8% in the target group. The novelty of community service is the integration of the Muhammadiyah dakwah bil-hal framework with an immunonutrition approach based on local Bima fruit that has never been reported in previous community service literature. These findings provide an empirical basis for the formulation of a community health intervention model integrated with Islamic values ​​and local food potential.